Double-blinded, randomized controlled trial comparing real versus placebo acupuncture to improve tolerance of diagnostic esophagogastroduodenoscopy without sedation: a study protocol - Knebel, Phillip; Schwan, Katja; Bruckner, Thomas; Seiler, Christoph; Plaschke, Konstanze; Streitberger, K.; Schaible, Anja; Bopp, Christian (Trials, 2011)
Sedation prior to performance of diagnostic esophagogastroduodenoscopy (EGDE) is widespread and increases patient comfort. But 98% of all serious adverse events during EGDEs are ascribed to sedation. The S3 guideline for sedation procedures in gastrointestinal endoscopy published in 2008 in Germany increases patient safety by standardization. These new regulations increase costs because of the need for more personnel and a prolonged discharge procedure after examinations with sedation. Many patients have difficulties to meet the discharge criteria regulated by the S3 guideline, e.g. the call for a second person to escort them home, to resign from driving and working for the rest of the day, resulting in a refusal of sedation. Therefore, we would like to examine if an acupuncture during elective, diagnostic EGDEs could increase the comfort of patients refusing systemic sedation.
Gesehen am 10.10.2022